Treadmill training of rats after sciatic nerve graft does not alter accuracy of muscle reinnervation - Barham, Mohammed; Andermahr, Jonas; Majczyński, Henryk; Sławińska, Urszula; Vogt, Johannes; Neiss, Wolfram F. (Frontiers in Neurology, 2023)
Background and Purpose: After peripheral nerve lesion, surgical reconstruction facilitates axonal regeneration and motor reinnervation. However, functional recovery is impaired by aberrant reinnervation. Material and Methods: We tested whether training therapy by treadmill exercise (9x250 m/week) before (run-idle), after (idle-run), or both before and after (run-run) sciatic nerve transplantation improves the accuracy of reinnervation in rats. Female Lewis rats (LEW/SsNHsd) were either trained for 12 weeks (run), or not trained (kept under control conditions, idle). The right sciatic nerves were then excised and reconstructed with 5 mm of a congenic allograft. One week later, training started in the run-run and idle-run groups for another 12 weeks. No further training was conducted in the run-idle and idle-idle groups. Reinnervation was measured using the following parameters: counting of retrogradely labeled motoneurons, walking track analysis and compound muscle action potential (CMAP) recordings. Results: In intact rats, the common fibular (peroneal) and the soleus nerve received axons from 549±83 motoneurons. In the run-idle group, 94% of these motoneurons had regenerated 13 weeks after nerve transplantation. In idle-run animals, 81% of the normal number of motoneurons had regenerated into the denervated musculature and 87% in both run-run and idle-idle groups. Despite reinnervation, functional outcome was poor: walking tracks indicated no functional improvement of motion in any group. However, in the operated hindlimb of run-idle rats, the CMAP of soleus muscle reached 11.9mV (normal 16.3mV), yet only 6.3 – 8.1mV in the other groups. Conclusion: Treadmill training did not alter the accuracy of reinnervation nor functional recovery, pre-operative training (run-idle) lead to a higher motor unit activation after regeneration.